2016
DOI: 10.1111/dme.13163
|View full text |Cite
|
Sign up to set email alerts
|

Distal lower limb strength is reduced in subjects with impaired glucose tolerance and is related to elevated intramuscular fat level and vitamin D deficiency

Abstract: Aim To quantify muscle strength and size in subjects with impaired glucose tolerance (IGT) in relation to intramuscular non-contractile tissue, the severity of neuropathy and vitamin D level. Methods A total of 20 subjects with impaired glucose tolerance and 20 control subjects underwent assessment of strength and size of knee extensor, flexor and ankle plantar and dorsi-flexor muscles, as well as quantification of intramuscular non-contractile tissue and detailed assessment of neuropathy and serum 25-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
3
4
0
Order By: Relevance
“…The association of abnormal LDI Flare and QTT testing with mixed fiber neuropathy, as reflected by the clinical and electrophysiological examinations, is in agreement with previous studies[4,5,1214]. Patients with abnormal small fiber testing in our cohort, had more frequent limb muscle weakness, reduced vibration and proprioception perception, and absent ankle reflexes on the neurological examination, indicating concomitant large fiber impairment.…”
Section: Discussionsupporting
confidence: 92%
“…The association of abnormal LDI Flare and QTT testing with mixed fiber neuropathy, as reflected by the clinical and electrophysiological examinations, is in agreement with previous studies[4,5,1214]. Patients with abnormal small fiber testing in our cohort, had more frequent limb muscle weakness, reduced vibration and proprioception perception, and absent ankle reflexes on the neurological examination, indicating concomitant large fiber impairment.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with our recent finding that people with Type 2 diabetes had a significantly reduced lower limb muscle strength, which was related to the severity of neuropathy but not to the level of vitamin D [7]. Although, in people with IGT we have recently shown a significant reduction in distal muscle strength, which was associated with increased intramuscular non-contractile tissue, small-fibre neuropathy and vitamin D deficiency [12].…”
Section: Discussionsupporting
confidence: 92%
“…Whilst the present results confirm previous findings of a reduction in ankle joint strength and power during walking in people with Type 2 diabetes , we also showed that participants with IGT had a reduction in ankle joint power during walking. These findings are supported by our recent data showing a significant weakness of the distal ankle plantar flexors in people with Type 2 diabetes and people with IGT .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Vitamin D deficiency and insufficiency, when combined typically defined as 25(OH)D concentrations < 50 nmol/L, are associated with muscle atrophy and deficits in muscle strength in several clinical models (Sato et al, 2005;Tagliafico et al, 2010;van Langenberg et al, 2014;Almurdhi et al, 2017;Bang et al, 2018). While many studies of vitamin D deficiency and insufficiency focus on its impact on protein synthesis and degradation, there is also a growing body of evidence to suggest that vitamin D supplementation in deficient individuals improves measures of mitochondrial density and function (Sinha et al, 2013;Rana et al, 2014).…”
Section: Vitamin D and Mitochondrial Healthmentioning
confidence: 99%